2007
DOI: 10.1375/bech.24.4.183
|View full text |Cite
|
Sign up to set email alerts
|

Processing of Emotional Faces in Children and Adolescents With Anxiety Disorders

Abstract: The purpose of this study was to test whether children and adolescents with anxiety disorders exhibit selective processing of threatening facial expressions in a pictorial version of the emotional Stroop paradigm. Participants named the colours of filters covering images of adults and children displaying either a neutral facial expression or one displaying the emotions of anger, disgust, or happiness. A delay in naming the colour of a filter implies attentional capture by the facial expression. Anxious partici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
29
0
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 42 publications
2
29
0
2
Order By: Relevance
“…Gifford-Smith and Brownell [27] pointed out that peer acceptance is most critical in elementary school and decreases with age. Accordingly, children may process adult and child-posed faces differently, as suggested by Benoit et al [11]. Three studies did not report difference between child and adult faces when anxious and non-anxious children completed ForcedChoice (FC) tasks [22,23,25].…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…Gifford-Smith and Brownell [27] pointed out that peer acceptance is most critical in elementary school and decreases with age. Accordingly, children may process adult and child-posed faces differently, as suggested by Benoit et al [11]. Three studies did not report difference between child and adult faces when anxious and non-anxious children completed ForcedChoice (FC) tasks [22,23,25].…”
Section: Introductionmentioning
confidence: 99%
“…Concerning the extend of the biases, some studies observed a slower response for angry faces solely [12] while others reported longer RT also for happy faces [11,15] and even for neutral faces [11]. Such inconsistencies may be explained by the fact that some paradigms presented adult faces [12], mixed child and adult faces [11] or schematic faces [14,15]. When comparing child and adult faces, Benoit et al [11] reported slower colour naming, meaning enhanced interferences, for adult faces than for child faces, irrespective of facial expressions and anxiety levels.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations